The Burden of Progressive Supranuclear Palsy on Patients, Caregivers, and Healthcare Systems by PSP Phenotype: A Cross-Sectional Study - Pillas, Demetris; Klein, Alexander; Gasalla, Teresa; Avbersek, Andreja; Thompson, Alexander; Wright, Jack; Mellor, Jennifer; Scowcroft, Anna (Frontiers in Neurology, 2022)
Progressive supranuclear palsy (PSP) is a rare, relentlessly progressive, ultimately fatal neurodegenerative brain disease. The objective of this study was to assess the burden of PSP on patients, caregivers, and healthcare systems by PSP phenotype. Data were drawn from the Adelphi PSP Disease Specific Programme™, a cross-sectional study of neurologists and people living with PSP in the United States of America, France, Germany, Italy, Spain, and the United Kingdom. All people living with PSP with a reported phenotype were included. PSP phenotype was reported for 242 patients (mean age: 70.2 years, 58% male): PSP-Richardson's syndrome, n = 96; PSP-predominant Parkinsonism, n = 88; PSP-predominant corticobasal syndrome, n = 28; PSP-predominant speech/language disorder, n = 12; PSP-progressive gait freezing, n = 9; PSP-predominant frontal presentation, n = 9. Most patients reported impaired cognitive, motor, behavioral and ocular functionality; 67–100% of patients (across phenotypes) had moderate-to-severe disease at the time of data collection. Post-diagnosis, the majority were provided with a visual and/or mobility aid (55–100%, across phenotypes), and/or required home modification to facilitate their needs (55–78%, across phenotypes). Patients required multiple types of healthcare professionals for disease management (mean 3.6–4.4, across phenotypes), and the majority reported receiving care from at least one caregiver (mean 1.3–1.8, across phenotypes). There is a high burden on patients, caregivers, and healthcare systems across all PSP phenotypes. Although phenotypes manifest different symptoms and are associated with different diagnostic pathways, once diagnosed with PSP, patients typically receive similar care.